2014
DOI: 10.1080/01457632.2014.923978
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Convection and Radiation Heat Transfer in a Horizontal Duct with Variable Wall Temperature

Abstract: In this research, experiments are performed to study the laminar flow mixed-convection heat transfer with radiation effects for a hydrodynamically fully developed and thermally developing airflow in a horizontal duct. The duct cross section is made of two differentially heated isothermal vertical walls and two adiabatic horizontal walls with aspect ratios 1 and 0.5. The total heat transfer from the hot wall to the cold wall of the duct depends on the mixed convection and also on the surface radiation heat tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Sadik et al [20] reported on different Nusselt number correlations for hydro-dynamical and thermal fully developed flow for combined free and forced convection heat transfer in horizontal and vertical circular tubes subjected to uniform wall heat flux conditions as well as uniform wall temperature boundary conditions. Ganesan, et al [21] experimentally investigated the effects of laminar flow mixed-convection and surface-radiation heat transfer in a horizontal duct. They found that the surface temperatures were affected by the heat flux and emissivity of the walls, Reynolds number and length of the duct.…”
Section: Introductionmentioning
confidence: 99%
“…Sadik et al [20] reported on different Nusselt number correlations for hydro-dynamical and thermal fully developed flow for combined free and forced convection heat transfer in horizontal and vertical circular tubes subjected to uniform wall heat flux conditions as well as uniform wall temperature boundary conditions. Ganesan, et al [21] experimentally investigated the effects of laminar flow mixed-convection and surface-radiation heat transfer in a horizontal duct. They found that the surface temperatures were affected by the heat flux and emissivity of the walls, Reynolds number and length of the duct.…”
Section: Introductionmentioning
confidence: 99%